A Contribuição da governança para a competitividade sistêmica no segmento de frango de corte: um estudo na Cooperativa Agroindustrial Consolata-Copacol - Silveira, Tânia Maria Smaniotto (2006)
The objective of this work is to analyze the contribution of the administration way adopted in the Integrated Complex Avicola of the Agroindustrial Cooperative – Copacol to the systemic competitiveness maintenance from 1990 to 2004. The Industrial Economy premises under the focus of Economy of the Costs of Transaction – ECT, originated in Coase (1937), and later extended with the Teacher Oliver Williamson (1989) contributions are used. The theorist referential presents the distinction between the agribusiness and agroindustrial systems. It analyzes the agroindustrial chain of broiler chicken expanding itself in the integration system explanation which is used in the South region of the country. It presents the systemic competitiveness in the static, dynamical and systemic approaches. In a short way, the competitiveness pattern in the industrial groups is analyzed. Through a short historic, a conceptual approach and its orientating principles the theorist referential is ended with the cooperatives as well as the organizational characteristics. The central hypothesis of this study considers that the competitiveness of Avicola Integrated Complex of the Agroindustrial Cooperative Consolata – Copacol is based in the administration capacity by means of hybrid ways through the contratualization of the agents: processing agroindustrial and integrated product. In this way, the administration used contributes to the confrontation of the competitive market in which one the Cooperative is inserted maintaining the systemic competitiveness of the Avicola Integrated Complex without compromising the orientating principles of the Cooperative. The contractual hybrid way used is adopted due to the complex and technical structure in which the productive processes of broiler chicken are involved. In this study is relevant to understand that the productive organization is a cooperative so the organizational characteristics differ from a marketing productive organization. The welfare of the associates and the maintenance of the cooperative principles are over the objective of the profit as occurs in a capitalist marketing society. The cooperative, being able to compete in the market, allows the autochthonous resources using, the democratic behavior and the interest by the collectivity. The cooperatives inserted in a strongly competitive market present in the same time the economical dimension and the results, and a social one being the efficiency an essential element in its enterprises. Through this research can be concluded that the competitiveness of the Integrated Complex Avicola of the Agro-industrial Cooperative Consolata – Copacol is based on the capacity of administration by means of hybrid forms of administration, through the contratualization among the integrator aviculture agents and agroindustrial integrator, and that this contributes for the confrontation of the competitive market where the Cooperative is inserted, keeping the systemic competitiveness of the Integrated Complex Avicola without compromising the orientating principles of the Cooperative. It is concluded that there is relation between administration structures and systemic competitiveness, and that the form of used administration contributes for the systemic competitiveness of the activity through the reduction of the transaction costs. Keywords: Administration; Systemic Competitiveness; Economy of the Costs of Transaction. Cooperatives.